GAME FORMS IN THE PRACTICE OF TEACHING RUSSIAN AS A FOREIGN LANGUAGE IN THE 4th GRADE OF A SCHOOL IN UZBEKISTAN - Ju.Ju. Danilova; Sh.Sh. Rahmonova (Многоязычие в образовательном пространстве)
This article describes the use of gaming technologies in the lessons of Russian as a foreign language for students of the 4th grades in Uzbek schools. The purpose of this study is to identify and describe the competence-oriented potential of gaming activities in the process of forming linguistic, communicative and meta-subject competencies of younger schoolchildren at the stage of consolidating the studied material in the lessons of Russian as a foreign language. The paper presents specific examples of the inclusion of lexical, grammatical and communicative games at various stages of the lesson of Russian as a foreign language in a school in Uzbekistan. The authors describe some games, such as «Guess who I am», «Even more», «Useful doctor’s advice», which contribute to the formation and development of subject and non-subject competencies of younger schoolchildren. Such games allow to develop the subject competence of the schoolchildren (expand their vocabulary, develop dialogue speech, improve the skills of using grammatical structures, etc.); they also help to understand social roles and behaviours in various situations, promote improvisation, and develop creativity. The analysis carried out from the point of view of a competence-based approach to learning allowed us to conclude that the use of game forms of learning in the practice of teaching RCT in the 4th grade of a school in Uzbekistan has a high methodological and competence potential. Play activity creates conditions for the comprehensive development of language, communicative, cognitive, educational and other key competencies of younger schoolchildren, as well as helps to increase their motivation to learn Russian, promotes deeper involvement in the educational process and the studied material.